Flavone glycosides from Uraria crinita - Tran Duc Dai; Dao Duc Thien; Nguyen Thanh Tam (Vietnam Journal of Science, Technology and Engineering, 2021)
A common edible herb found in all regions of Vietnam is Uraria crinita (L.) DC. (Leguminosae). It has been used as a vegetable or in folk medicine to treat lung disorders, sprains, bruises, diarrhea, and rheumatism. Pharmacological studies have shown that U. crinita possesses a range of medicinal qualities, including as antioxidant, anti-inflammatory, and osteogenic activity, as well as the ability to lessen ulcers brought on by stress. Numerous substances, including flavonoids, triterpenes, megastigmanes, and nucleosides, have been identified as this plant’s active ingredients. Four flavone glycosides including apigenin 7-O-β-glucoside (1), chrysoeriol 7-O-β-glucoside (2), rhoifolin (3), and 3’-methoxyapiin (4) were isolated from the n-butanol extract of the whole plant Uraria crinita collected in the Phu Tho province, Vietnam. Their structures were elucidated by 1D- and 2D-NMR spectra and compared with those reported in the literature. The structures of compounds 1-4 were determined by spectroscopic methods and comparison with published data. Compounds 1-3 were obtained from the genus Uraria for the first time. This is the first report of these compounds from the genus Uraria.